Full Size Two-Layer Steel Frame–Exterior Wall Panel Shaking-Table Test - Beibei Yang; Zhenbao Li; Ping Liu; Hua Ma; Jiulong Yang; Zhicheng Kang (Buildings, 2024)
A cantilever block wall-panel attachment strip (CBW) flexible connection node was designed to connect precast concrete (PC) exterior wall panels to steel frames. To investigate the performance of the CBW flexible connection node and PC exterior wall panels during earthquakes, a partial two-storey steel frame was extracted from an actual engineering structure, and a full-scale steel frame–exterior wall panel shaking-table model was designed. Two sets of shaking-table tests were conducted under seismic intensity 7, 8, and 9 (Chinese Seismic Intensity Scale) earthquakes. The acceleration and displacement responses of the composite wall panel, open window panel, and integral wall panel along the in-plane and out-of-plane motions were analysed. The acceleration amplification factors of the PC exterior wall panels ranged from 0.753 to 1.400 (in-plane) and from 0.998 to 2.199 (out-of-plane). The CBW flexible connection node had a deformation capacity that could coordinate the deformation of the exterior wall panel and prevent severe damage. The surfaces of the PC exterior wall panels remained intact during a very strong seismic intensity 9 earthquake.